Design of data validation solutions using high density 2D colored codes and a (2,2) xor-based color interference visual cryptography scheme - Melgar, Max Eduardo Vizcarra (2018)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2018.